The development intellectual activity of students-philologist in the perfomance of the IWS (Eurasian Journal of Philology Science and Education, 2019)
This article considers organization of independent work of students-philologists as one of the leading forms of development of students’ intellectual activity. According to modern standards of education, independent work of students is given a great role in the educational process, that’s why the tasks for this form of monitoring the assimilation of knowledge should be carefully developed and controlled by the lecturer. In this regard, the connection between the functions of the brain as a kind of taxonomy of information processing and the connection with the pedagogical taxonomy bloom, as well as its updated version, successfully used by teachers in the educational process. The article gives a brief overview of the structural analysis and methods of linguistic research of concepts. The concept of “Soul”is considered. Its main characteristics are revealed. It is proved that the concept of Soul is a dynamic concept and reflects pagan, Christian, scientific and naive ideas of the Russian people. Phraseological units with the lexeme “soul”, acting as a means of language conceptualization of the surrounding world, are investigated. The study of concepts is of great importance for understanding the culture and worldview of both one nation and humanity as a whole. The research methodology of the concept is arranged in five major stages, which also contributes to the hierarchical performance of tasks from tackling more manageable problems to thornier, thus stimulating and developing students’ intellectual activity.